The Influence of Product Innovation, Promotions, and Prices on the Decision to Purchase Oppo Brand Smartphones at the Alya Phones Shop, Kotapinang - Fatah, Suadim; Fitri, Meisya; Halim, Abdul (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
This research aims to analyze the Influence of Product Innovation, Promotion, and Price on Purchase Decisions for Oppo Oppo-brand smartphones at the Alya Mobile Shop, Kotapinang. The research method used in this research is quantitative. In this research, the population is consumers of Oppo Brand Smartphones at the Alya Mobile Shop, Kotapinang as many as 56 people. The data collection techniques used were observation, documentation studies, and questionnaires. The analytical method for this research is multiple linear regression with the SPSS program. The research results prove that Product Innovation positive and significant effect on the decision to purchase an Oppo Brand Smartphone at the Alya Mobile Shop, Kotapinang. Positive promotion and significant effect on the decision to purchase an Oppo Brand Smartphone at the Alya Mobile Shop, Kotapinang. Positive price and significant effect on the decision to purchase an Oppo Brand Smartphone at the Alya Mobile Shop, Kotapinang. Product Innovation, Promotion, and Price simultaneously have a positive and significant effect on the decision to purchase an Oppo Brand Smartphone at the Alya Mobile Shop, Kotapinang. The coefficient of determination is 0.524, meaning that purchasing decisions can be explained by the Product Innovation variable (X1), Promotion (X2), and price (X3) amounting to 52.4%, while the remaining 47.6% can be explained by other variables not examined in this study.